THE HARBOUR DEFENCE MOTOR LAUNCHES - Rice, W.H. (Scientia Militaria - South African Journal of Military Studies, 2012)
One of the handiest small craft to emerge from the Second World War was the 72 fet Harbour Defence Motor Launch. It’s purpose was to patrol harbours and their approaches and to guard against attack by swimmers or underwater vehicles such as ’chariots’ or even submarines. For this task the craft was fitted with a small ASDIC outfit and carried eight depth charges. Surface armament comprised a three-pounder gun on the foredeck, twin Lewis guns on the bridge and a 20 mm Oerlikon aft.